Cross-country evidence of consumers’ perception of food from animals fed on insects in DR Congo, Mali, and Niger - Dontsop-Nguezet, P.; Nyamuhirwa, D.A.; Shiferaw, F.; Manyong, V.; Sissoko, D.; Moussa, B.; Kouakou, A.G.; Zakari, S.; Abdoulaye, T. (Elsevier, 2024)
Insects can represent a valuable and cost effective source of animal feed in Africa. Recently, the interest in incorporating black-soldier fly larvae (BSFL) in animal feed has increased tremendously. However, many factors, including food neophobia and social and cultural context may affect consumers' perception of insect-technologies-derived food products. This study shed light on consumers' perception of the usage of BSFL as animal feed and consumption, buying, and commercialization of food from animals fed on BSFL in DR Congo, Mali, and Niger. We used data from 1560 consumers that were analyzed applying parametric and non-parametric tests and the generalized ordered logit model. Our findings show that about 87 % of respondents consider that consuming food from animals fed on BSFL is acceptable and 34 % accept buying eggs, fish, and meat from animals fed on BSFL. However, about 40 % of consumers recommend the label differentiation of BSF-technologies-derived food products and they also expect a lower price than conventional animal feed products. The analysis of factors driving consumers' readiness to buy BSF-derived food products have revealed that effective market penetration of BSF-technologies-derived food products could be achieved with great awareness creation, targeting farming households, married and literate heads. Furthermore, strategic communication and intensive sensitization through farmers' associations will be crucial. Finally, credit access and income diversification are also necessary to support consumers’ choices toward sustainable food habits built on bio-circular economy.